A randomized saline-controlled trial of NASHA hyaluronic acid for knee osteoarthritis. (February 2014) - Arden, Nigel K.; Åkermark, Christian; Andersson, Mats; Todman, Martin G.; Altman, Roy D.
Abstract Objective: NASHA hyaluronic acid is administered as a single intra-articular injection to treat the symptoms of osteoarthritis (OA). In a previous trial, post-hoc analysis indicated that NASHA provides significantly greater pain relief than saline in patients with OA confined to the study knee. We aimed to evaluate the safety and efficacy of NASHA in patients with unilateral knee OA. Research design and methods: This was a randomized, double-blind, saline-controlled trial. All patients had knee OA confirmed by American College of Rheumatology criteria and a WOMAC pain score of 7–17 in the study knee, but no pain in the previous 3 months in the non-study knee. Treatment comprised a single intra-articular injection of NASHA or saline control. The follow-up period was 6 weeks. Clinical trial registration: ClinicalTrials.gov NCT01806207. Main outcome measures: The primary efficacy endpoint was the responder rate, defined as the percentage of patients with ≥40% improvement from baseline in WOMAC pain score and an absolute improvement of ≥5 points. Results: A total of 218 patients received study treatment (NASHA: 108, saline: 110). In the main intention-to-treat (ITT) analysis, no statistically significant difference in responder rate was found between the two groups at 6 weeks (NASHA: 30.6%; saline: 26.4%). A post-hoc subgroup analysis of patients without clinical effusion in the study knee at baseline showed a significantly higher 6 week responder rate with NASHA than with saline: 40.6% versus 19.7% (p = 0.0084). A total of 68 adverse events were reported among 44 patients in the NASHA group, compared with 69 adverse events among 44 patients in the saline group. The main weakness of the study was the short, 6 week follow-up duration. In addition, image guidance was not used to ensure injection as intended into the intra-articular space. Conclusions: Single-injection NASHA was well tolerated and, although there was no significant benefit versus saline control in the primary analysis, post-hoc analysis showed a statistically significant improvement in pain relief at 6 weeks among patients without clinical effusion at baseline.